Building Students’ English Foundation Through A Contextual And Practical Pedagogical Grammar Approach At SMP IT Imam Syafi'i Cendikia Pekanbaru - Safriyani Novitri Yani; Khulaifiyah Khulaifiyah; Novia Nazirun; Rima Maulani Kurnia; Yayang Mei Sari Samosir (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The goal of this community service program at SMP IT Imam Syafi'i Cendikia Pekanbaru was to help students improve their practical English skills, especially their speaking and writing. Even though students had learnt grammar in a formal setting before, it was clear from observations that there was a big difference between what they knew about grammar and how well they could use it in real-life situations. A contextual and applicative Pedagogical Grammar approach was implemented to tackle this issue, in accordance with the Merdeka Belajar Kampus Merdeka (MBKM) framework that priorities flexible, meaningful, and student-centered learning. The program included socialization, training for teachers, putting what they learnt into practice in the classroom, mentoring, and regular evaluations. Grammar lessons were part of real-life communication tasks like role-playing, group discussions, and writing. The learning materials were made more relevant to students' lives by using themes like empathy, bullying awareness, and hobbies. The results show that students' English skills have gotten a lot better. Students showed more confidence when speaking English, wrote messages and short texts with more accuracy and fluency, and used grammatical structures better in real-life conversations. Teachers also said that using interactive and context-based methods to teach grammar made them more effective. In general, using contextual Pedagogical Grammar has been shown to improve students' ability to communicate and close the gap between knowing grammar and using it in real life. This method helps MBKM reach its goals and gets students ready to meet the demands of global communication with more linguistic confidence and skill.